#### Answer

Net change is -21

#### Work Step by Step

$g(t) = 1 - t^2$
$g(-2) = 1 - (-2)^2 = 1 - (4) = -3$
$g(5) = 1 - (5)^2 = 1 - (25) = -24$
$g(5)-g(-2) = (-24) - (-3) = -21$
Net change is a decrease by 21

Published by
Brooks Cole

ISBN 10:
1305071751

ISBN 13:
978-1-30507-175-9

Net change is -21

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.